Educação, trabalho e capital: um estudo sobre a precariedade do trabalho na indústria da construção civil em Fortaleza - Almeida, Ronaldo de Sousa (2009)
This dissertation examines the precariousness of work in the sector of construction industry in Fortaleza in the period 2006 to 2008. We seek to understand, we will examine the recent restructuring of production (from the final decades of the twentieth century), the implications of those changes in concrete terms in working-class life in Brazil and specifically in the city of Fortaleza, with reference to the sector productive construction. Within this context, the study aims to examine to what extent such changes affect the relationship between work and education into the fabric of social relations of the working class of that sector. In this sense, the work dives in search of understanding of the following experienced by (the) employees (the) political consciousness, working conditions, experience of education and expectations for the future. The study acknowledges (among other aspects of this complex world) to build a working class culture, elaborated by the workers and involving them in such a way that makes it, often alternative ways of seeing and / or less tortuous for you at the same time in following their paths now outlining elements of resistance now conformist. It follows, too, which is the fundamental organization of (the) employees (as) in trade unions and the struggle to claim their rights and as an element of pressure to educate the state to institute them.